(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Gall stone disease is a common problem affecting human being. Laparoscopic cholecystectomy (LC) has become gold standard for the surgical treatment of gallbladder disease over the past two decades. Preoperative prediction of the risk of conversion or difficulty of operation is an important aspect of planning laparoscopic surgery. Various scoring methodologies have been suggested using different criteria from time to time, which have also increased the controversy regarding the application of different scoring systems. The aim of our study was to establish the validity of the scoring system devised by Randhawa et al in our hospital scenario. Material and Methods: - This study was conducted in DHQ Hospital Mirpur. A total of 37 patients were enrolled in the study from February 2024 to August 2024. Patients were assessed on the scoring system that was designed by Randhawa and Pujahari. Later all the scores were added up in order to get a total score. Finally, patients were categorized into risks-based scoring system into no risk, moderate risk and high-risk categories. Ethical review committee approval was obtained before conducting the study. Chi square test was performed to evaluate the significant relationship between preoperative scores and pre-operative outcomes’-value of <0.05 was taken as statistically significant. Results: - A total of 37 patients were enrolled in the study from February 2024 to August 2024. Ethical review committee approval was obtained before conducting the study. There was significant association was found between previous abdominal scar and difficult laparoscopic surgery with p-value of 0.02. Twenty-three patients scored easy (62.2%) and only fourteen (37.8%) scored difficult while no patient scored very difficult in our study. Prediction came true in 71.4% for easy and 50% difficult cases; there were no cases with a score above 10. Conclusion: - Previous abdominal scar is an important finding and was found to be statistically significant in predicting difficult laparoscopic surgeries. However, study with large sample size could provide us better understanding and good assessment of other factors associated with difficult laparoscopic surgeries.